Process optimization for the manufacturing of flax seed powder enriched Kalakand - Kumar, Hemant; Hooda, Ankita (Indian Journal of Dairy Science, 2024)
Kalakand is made traditionally, with no concern for the quality of the raw materials as well as no functional properties. This product is consumed by a large sector of population, hence enriching it with flaxseed could impart many functional properties. Flaxseed is well-known for its nutritional benefits. It is recognized for its high quantities of alpha-linolenic acid, lignan, a phytoestrogen molecule, and soluble as well as insoluble fibre. Jaggery includes 60-85% sucrose, 5- 15% glucose and fructose, 0.4 % protein, 0.1 g fat, 0.6 to 1.0 g minerals (8 mg calcium, 4 mg phosphorus, and 11.4 mg iron), traces of vitamins and amino acids, and around 383 kcal of energy per 100 g of jaggery. Flax seed is a functional food and generally help in treatment of numerous diseases. In terms of sensory qualities compared to the other treatments, T1 (with 1% flaxseed powder) was observed to have the required quality. The results show that enriched kalakand was analyzed to have decreased moisture, carbohydrate, and pH while increased content of protein, fat, ash, total solids, acidity, and antioxidant activity as compared to the control. The heart and circulatory systems benefit from flaxseed in all forms. The another important component was jaggery, which is not only a natural sweetener but has been shown to reduce the risk of heart disease, cancer, control blood pressure, liver detoxification, cataracts, and many inflammatory changes, also.